Time Perspective Theory; Review, Research and Application: Essays in Honor of Philip G. Zimbardo - Stolarski, Maciej (Springer, 2015)
This book is about time and its powerful influence on our personal and collective daily life. It presents the most comprehensive and up-to-date overview of contemporary knowledge on temporal psychology inspired by Zimbardo's work on Time Perspective (TP). With contributions from renowned and promising researchers from all over the globe, and at the interface of social, personality, cognitive and clinical psychology, the handbook captures the breadth and depth of the field of psychological time. Time perspective, as the way people construe the past, the present and the future, is conceived and presented not only as one of the most influential dimensions in our psychological life leading to self-impairing behaviors, but also as a facet of our person that can be de-biased and supportive for well-being and happiness. Written in honor of Philip G. Zimbardo on his 80th birthday and in acknowledgement of his leading role in the field, the book contains illustrations of the countless studies and applications that his theory has stimulated, and captures the theoretical, methodological and practical pathways he opened by his prolific research.